2022
DOI: 10.3390/pharmaceutics14102253
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Somatostatin-Expressing Neurons in the Lateral Septum Improves Stress-Induced Depressive-like Behaviors in Mice

Abstract: Depression is a debilitating mood disorder with highly heterogeneous pathogenesis. The limbic system is well-linked to depression. As an important node in the limbic system, the lateral septum (LS) can modulate multiple affective and motivational behaviors. However, the role of LS in depression remains unclear. By using c-Fos expression mapping, we first screened and showed activation of the LS in various depression-related behavioral tests, including the forced swim test (FST), tail suspension test (TST), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 105 publications
0
6
0
Order By: Relevance
“…Previous studies indicate that SST can mediate inhibitory responses primarily at dendritic sites within excitatory neuronal networks (67-69) and also at axonal sites within the MHb-IPN pathway (62). In addition, SST function is implicated in anxiety-like behavior (70,71) and behavioral responses mediated by chronic stress (72)(73)(74). Our scRNAseq data identified IPN stress-activated neurons as highly enriched for SST, suggesting that the IPN is part of the SSTergic network underlying self-grooming.…”
Section: Discussionmentioning
confidence: 53%
“…Previous studies indicate that SST can mediate inhibitory responses primarily at dendritic sites within excitatory neuronal networks (67-69) and also at axonal sites within the MHb-IPN pathway (62). In addition, SST function is implicated in anxiety-like behavior (70,71) and behavioral responses mediated by chronic stress (72)(73)(74). Our scRNAseq data identified IPN stress-activated neurons as highly enriched for SST, suggesting that the IPN is part of the SSTergic network underlying self-grooming.…”
Section: Discussionmentioning
confidence: 53%
“…We identified 14 molecularly defined cell types in the septum (2 glutamatergic and 12 GABAergic), which we determined by evaluating cluster stability over multiple clustering granularities (Figure 1C, S1G). Among these neurons, we found clusters that corresponded to previously-identified LS cell types, including neurotensin-(Nts+; Gaba8), somatostatin-(Sst+; Gaba11), corticotropin-releasing hormone receptor 2-(Crhr2+; Gaba5) and dopamine receptor 3expressing (Drd3+) neurons [19][20][21][32][33][34][35] . Crhr2 expression was limited to the Gaba5 subcluster, but Nts and Sst expression were more promiscuous.…”
Section: Resultsmentioning
confidence: 59%
“…Using in situ , in vivo , and ex vivo approaches, we demonstrated that spontaneous withdrawal induces LS- Nts activity in vivo, likely due to opioid-driven increases in glutamatergic signaling onto LS- Nts neurons. Opioid withdrawal is arguably a chronic stress state 1,3,22,61 , and other states of chronic distress, such as pain and chronic social defeat, elevate neuronal activity in the LS, including in LS- Nts , LS- Sst , and general LS GABAergic neurons 34,62,63 . We originally hypothesized that prolonged LS- Nts activation would be maladaptive, but our results indicated the opposite.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, groups of functionally distinct LS neurons have been characterized based on differences in the expression of neuropeptides and neurotransmitter receptors. For instance, somatostatin ( Sst) expressing neurons in the LSd have been implicated in the regulation of context-associated fear behaviors and are thought to be anxiolytic (An et al, 2022; Besnard et al, 2019; Li et al, 2022). In contrast, neurons expressing the corticotropin releasing hormone receptor 2 ( Crhr2 ) in the LSi are activated by threatening stimuli and are anxiogenic (Anthony et al, 2014; Hashimoto et al, 2022).…”
Section: Introductionmentioning
confidence: 99%